Case report: Osteo-oto-hepato-enteric syndrome caused by UNC45A deficiency - Wang, Ruixue; Wang, Yizhong; Yu, Ronghua; Xu, Wuhen; Zhang, Ting; Xiao, Yongmei (Frontiers in Genetics, 2023)
Background: Recently, UNC45 myosin chaperone A (UNC45A) deficiency was identified as a cause of osteo-oto-hepatoenteric syndrome (O2HE) characterized by congenital diarrhea, neonatal cholestasis, deafness, and bone fragility. To date, only a few O2HE cases have been reported in the literature. Case presentation: Here, we describe a child from China diagnosed with O2HE with novel compound heterozygous variants in UNC45A. The patient suffered with neonatal jaundice, cholestasis, and intractable diarrhea after birth. Laboratory tests revealed highly elevated levels of total serum bilirubin (TB), direct bilirubin (DB), and total bile acid (TBA). The patient was managed with ursodeoxycholic acid (UDCA) based treatments, and the clinical symptoms and abnormal liver functions were significantly relieved. The patient’s hearing is normal, and no sign of bone fragility was observed. Exome sequencing (ES) identified novel compound heterozygote variants c.292C>T (p.Arg98Trp)/c.2534-2545del (p.Leu845-Met848del) in UNC45A, which were inherited from her mother and father, respectively. Both variants are predicted to be deleterious by in silico predictors. Conclusions: We present an O2HE child from China with novel compound heterozygous variants in UNC45A. Our patient’s clinical manifestations were less severe than the previous reported cases, which expands the clinical spectrum of O2HE syndrome.